Recenze a anotace 2_2008 (Romano džaniben, 2008)
Lorenz Aggermann, Eduard Freudmann, Can Gülcü / Beograd GazelaDevla, Devla!Anna Rezková / Oáza křehkých dušíMatéo Maximoff / Sudba UrsitorůAndrzej Polakowski / Požegnanie taboru. Fotografie 1967RombaseRomlexRomani Project Manchester / The Romani Linguistics PageJán Šándor / CigliankaErich Maria Schneller / Zigeuner. Roma. Menschen